The Reality of Electronic Publishing for Faculty Members in the College of Science at the University of Basra - Saleh Nemeh Al -Shammari, Researcher. Mohammed; Ali Oreibi, Prof. Dr. Khuloud (Basra studies journal, 2022)
The research aims to define the concept of electronic publishing, its main characteristics, advantages, and disadvantages. It also aims to introduce the approved channels for academic electronic publishing, along with the time frame required for electronic publishing, the number of electronically published intellectual outputs over the past three years, using a documentary method in the theoretical aspect and a descriptive (survey) method in the practical aspect. A questionnaire tool was used to collect data, consisting of (5) axes distributed over (10) questions and distributed to faculty members at the College of Science, University of Basra, at a rate of (15%) of the total (362) faculty members. Percentage ratios were used to extract the results.